The use of computed radiography plates to determine light and radiation field coincidence. Issue 11 (8th October 2013) - Kerns, James R.; Anand, Aman
Abstract : Purpose: : Photo‐stimulable phosphor computed radiography (CR) has characteristics that allow the output to be manipulated by both radiation and optical light. The authors have developed a method that uses these characteristics to carry out radiation field and light field coincidence quality assurance on linear accelerators. Methods: : CR detectors from Kodak were used outside their cassettes to measure both radiation and light field edges from a Varian linear accelerator. The CR detector was first exposed to a radiation field and then to a slightly smaller light field. The light impinged on the detectorˈs latent image, removing to an extent the portion exposed to the light field. The detector was then digitally scanned. AMATLAB ‐based algorithm was developed to automatically analyze the images and determine the edges of the light and radiation fields, the vector between the field centers, and the crosshair center. Radiographic film was also used as a control to confirm the radiation field size. Results: : Analysis showed a high degree of repeatability with the proposed method. Results between the proposed method and radiographic film showed excellent agreement of the radiation field. The effect of varying monitor units and light exposure time was tested and found to be very small. Radiation and light field sizes were determined with an uncertainty of less than 1 mm, and light and crosshair centers were determined within 0.1 mm. Conclusions: : A new method was developed to digitally determine the radiation and light field size using CR photo‐stimulable phosphor plates. The method is quick and reproducible, allowing for the streamlined and robust assessment of light and radiation field coincidence, with no observer interpretation needed.